COACHING CLINIC MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA BAGI GURU SMP DI LANGSA SEBAGAI PENDUKUNG PENGEMBANGAN KARAKTER PESERTA DIDIK - Coryna Oktaviani; Seprianto Seprianto; Mentari Darma Putri (Jurnal Abdi Insani, 2023)
The Pancasila Student Profile Strengthening Project or commonly known as P5 is one of the strategies to realize national education goals. Strengthening character education through the Pancasila Student Profile Strengthening Project is very important because students live in the digital age and there is increasingly a decline in students' character. In its implementation, the existing conditions show that there are still many teachers who do not properly understand P5 activities and how to create P5 modules, including teachers at SMP Negeri 4 Langsa. The aim of this service activity is to increase teachers' knowledge, understanding, skills and creativity in creating P5 modules to support student character development. The form of service activities is education and coaching clinics which consist of preparation stages, implementation stages and evaluation stages. Pretest and posttest on 17 participants were carried out to determine the increase in participants' knowledge in making the P5 module to support student character development. Participant satisfaction with service activities was measured using a questionnaire consisting of 11 indicators. In the preparation stage, the service team has prepared all the equipment and educational materials or coaching clinic materials and coordinated with partners regarding the time and place of implementation. The results achieved from the implementation phase were the production of three P5 module products made by participants who were divided into three groups. The results of the evaluation stage by administering the pretest and posttest showed that there was an increase in participants' knowledge in making the P5 module in the high category with an n-gain value of 0.79. The results of the participant satisfaction questionnaire showed that 85.29% of participants were very satisfied while another 14.71% were satisfied with the service activities that had been carried out.